Pengelolaan Sumber Daya Alam dan Pelestarian Lingkungan Hidup dalam Perspektif Islam : Tinjauan Ayat-Ayat Alqur’an (Lembaga Pengembangan Kinerja Dosen, 2025)
The issue of environmental damage and excessive exploitation of natural resources is a global challenge that threatens the survival of creatures on earth. In Islam, the universe is seen as a creation of Allah SWT that must be protected and managed with moral and spiritual responsibility. This study aims to examine the concept of natural resource management and environmental preservation from an Islamic perspective through a review of the verses of the Qur'an. The method used is a literature study with a qualitative descriptive approach. The results of the study show that the Qur'an pays great attention to environmental preservation and places humans as caliphs who have the responsibility to maintain the balance of the ecosystem. Islamic values ​​such as monotheism, justice, trustworthiness, and the prohibition of damage (facade) are the basis of environmental ethics in Islam. Thus, environmental management in the Islamic perspective is not only oriented towards economic utilization, but also towards the preservation of Allah SWT's creation as a form of worship and obedience. This ecotheological awareness is important to be instilled in every human activity in order to create environmental sustainability for future generations.